2017
DOI: 10.1007/s40261-017-0554-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profiles of Ticagrelor Orodispersible Tablets in Healthy Western and Japanese Subjects

Abstract: Background and ObjectivesTicagrelor is an antiplatelet agent for patients with acute coronary syndrome or a history of myocardial infarction. Two studies compared pharmacokinetic profiles of orodispersible (OD) ticagrelor tablets versus immediate-release (IR) tablets in Western and Japanese subjects.MethodsBoth studies were open-label, randomized, crossover, single-center trials. Thirty-six healthy subjects (94% white, 6% other race; Western study NCT02400333) and 42 Japanese healthy subjects (Japanese study N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…A total of 64 records were screened, of which 14 studies were selected for qualitative analysis . Among the 14 studies (Table ), 10 tested ticagrelor (crushed or chewed) alternative administration, 2 tested the effect of crushed clopidogrel, 1 of crushed prasugrel and 1 of both crushed clopidogrel and ticagrelor . Only 5 were selected for quantitative efficacy analysis, because only these studies reported PRU value at 1 h and had a control arm with standard P2Y12‐receptor inhibitor administration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 64 records were screened, of which 14 studies were selected for qualitative analysis . Among the 14 studies (Table ), 10 tested ticagrelor (crushed or chewed) alternative administration, 2 tested the effect of crushed clopidogrel, 1 of crushed prasugrel and 1 of both crushed clopidogrel and ticagrelor . Only 5 were selected for quantitative efficacy analysis, because only these studies reported PRU value at 1 h and had a control arm with standard P2Y12‐receptor inhibitor administration.…”
Section: Resultsmentioning
confidence: 99%
“…All these studies were focused on ticagrelor crushed/chewed administration. Of the remaining 9 studies excluded from quantitative analysis, but included in the systematic review, 3 lacked a control group, whereas 6 lacked of efficacy measurement (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results have been described in healthy volunteers with reports of a bioequivalence between the orodispersible and the immediate release tablet. 56 Nevertheless, comparison between the orodispersible and the crushed, film-coated tablets of ticagrelor has not been performed so far.…”
Section: Crushed P2y 12 Receptor Inhibitors Tablets In Out-of-hospitamentioning
confidence: 99%
“…Ticagrelor has the advantage of a mortality reduction demonstrated in the PLATO trial 4 with a fast onset and offset of action 2 .Moreover, off-label use of ticagrelor is common in high-risk elective PCI such as left main stenting, stenting in diabetics, multiple stenting, high risk of stent thrombosis and lack of clopidogrel pretreatment 21 . However, this off-label use is not supported by any data.Ticagrelor validated loading dose in PCI for ACS is 180 mg with oral administration (2 tablets of 90 mg) or with crushed or orodispersible tablets27,28 followed by 90 mg twice daily maintenance dose (MD) was chosen at the time of design of the ALPHEUS trial. Beside the ISAR-REACT 5 trial 29 recently published and conducted in an ACS population, there is no trial that compared ticagrelor to prasugrel in the setting of elective PCI.…”
mentioning
confidence: 99%